The Crossed-Dipole Antenna with Torang-shaped Parasitic Elements and Circular Polarization for GPS Application - Amir Siahcheshm (مهندسی مخابرات جنوب)
This paper presents a circularly polarized (CP) printed crossed-dipole antenna for Global Positioning System (GPS) receptions in the L1 (1575 MHz) band. Its structure consists of two orthogonally printed dipoles, two integrated baluns to feed the dipoles, and a feed network connected to the baluns. The feeding network comprises a Branch-Line Coupler with two quadrature outputs. Accordingly, providing two orthogonal dipoles with a 90-degree phase difference leads to right-handed circular polarization (RHCP), a must for GPS applications. Four Torang-shaped parasitic elements have been used in the upper part of the dipole arms to improve the circular polarization of the antenna. Based on the practical results obtained with the technique, the antenna's Axial Ratio (AR) bandwidth is increased by about 21%. At the same time, the purity of the circular polarization can also be seen. The experimental results show that the proposed GPS antenna has an impedance bandwidth of 46.28% (from 1.327 to 2.126 GHz), an axial ratio bandwidth of 41.36% (from 1.329 to 2.022 GHz), and a maximum gain of 6.40 dB. The dimensions of the proposed antenna are compact, and this antenna has a stable radiation pattern. In the last step, the proposed GPS antenna is fabricated and tested in the antenna laboratory.